Digitalization Challenges and PAI Learning: Strengthening Digital Islamic Literacy as a Modern Spiritual Strategy at Senior High School - Kurniawan, Rikza Syahrial; Irham , Ananda Salsabiila; Istiqomah , Nefis Faiqotul; Syafi’i , Imam; Munawir, Munawir (Al Ulya: Jurnal Pendidikan Islam, 2026)
This study aims to understand how digital Islamic literacy serves as a modern spiritual tool for students experiencing digital fatigue at SMAN 1 Gedangan Sidoarjo. Digital fatigue has become a serious problem among teenagers, characterized by decreased motivation to study, stress, and spiritual exhaustion stemming from excessive social media use. This study uses a qualitative case study approach, employing data collection techniques such as observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles & Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that digitalization has an ambivalent impact on students' spirituality: on the one hand, it facilitates access to religious knowledge, but on the other hand, it causes distraction and mental fatigue (digital fatigue). Through the integration of digital Islamic literacy, PAI learning has successfully transformed from a lecture-based method to an interactive dialogue focused on reflecting on Islamic values in the virtual world. Digital Islamic literacy has been shown to strengthen critical thinking skills, spiritual awareness, and the ability to select and interpret religious content in context. The conclusion of this study confirms that digital Islamic literacy not only improves students' technological skills but also serves as a means of reactivating.